(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The article considers the essence of corporatization in the context of the formation of the integration economy. Emphasis is placed on the integrative feature of the economy. The theoretical essence of integration and its economic nature are revealed. The features of the economic system according to the system approach are revealed. Emphasis is placed on such properties of the economic system as: integrity, hierarchy and integrativity. It has been found that the integrative nature of the economy presupposes the possession of an economic system with such properties that are not inherent in its individual elements. It is emphasized that the formation of corporate ownership and the organization of economic relations have formed an adequate environment and initiated the process of consolidation in the economy. It is proved that the corporatization of the economy removes obstacles to the spatial framework and pace of economic development, forms a new corporate look of the market system and generates integration processes between companies. It is argued that corporatization generates integration processes in the economic system and finds expression in the consolidation of economic entities in the form of mergers and acquisitions. Consolidation has been found to be closely linked to market corporatization. The causal links of consolidation with the functioning of corporate business, which is a prerequisite for the development of an integrated economy, have been studied. It is emphasized that consolidation contributes to the integration processes of the state’s economic growth.